Iranian National Curriculum and the pre-university English textbook: the degree of compatibility of objectives - Mahmoudi, Leila; Abu Bakar, Kamariah (Australian International Academic Centre, 2014)
Textbooks are one of the important teaching materials in language teaching and a common resource for any teacher in helping students to learn English. Apart from being a learning tool, textbooks are considered as an important medium to realize curriculum goals and objectives. The purpose of this study is to investigate the amount of compatibility of the pre-university English textbook, which is prescribed by the ministry of education, with Iranian National Curriculum (INC) in terms of objectives and content of teaching. To this end, two instruments were used: A textbook evaluation checklist proposed by Ghorbani (2011), and the Iranian National Curriculum. The findings of the study revealed that the textbook was not in line with the curriculum in terms of objectives and content of teaching.